2008
DOI: 10.1021/jp711202q
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Hydrogen Sulfide Adsorption on Mo-Edge MoS2 Surfaces under Solid Oxide Fuel Cell Conditions

Abstract: We examine the degree to which sulfur-based fuel contaminants, such as hydrogen sulfide (H 2 S), can adsorb on the molybdenum sulfide-based anode of a solid oxide fuel cell (SOFC) under normal SOFC conditions. Our examination takes into account multiple adsorption/desorption events involving H 2 S and the fuel (H 2 ). By means of a kinetic model that allows us to approximate the rate of adsorbed oxygen formation based on experimental O 2-anion consumption at the triple-phase-boundary (TPB), we also consider th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…[40][41][42][43] Although further studies need to be done in order to fully unveil the processes occurring at these edges, some theoretical studies have already shown the possibility of their modification through adsorption and desorption processes. [52][53][54] Starting with the most stable 50% S zig-zag edges, 1,2-dithiolanes can directly bind to the exposed Mo at this edge, saturating and resulting in 100% S coverage with covalently attached species, preferentially in a binding configuration perpendicular to the edge (cf. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43] Although further studies need to be done in order to fully unveil the processes occurring at these edges, some theoretical studies have already shown the possibility of their modification through adsorption and desorption processes. [52][53][54] Starting with the most stable 50% S zig-zag edges, 1,2-dithiolanes can directly bind to the exposed Mo at this edge, saturating and resulting in 100% S coverage with covalently attached species, preferentially in a binding configuration perpendicular to the edge (cf. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[58,59] The change in the band structure of MoS 2 with the layer numbers can be attributed to quantum confinement and the resulting change in hybridization betweenM o4d z 2 orbitals and S3p z orbitals. [64,67] However, the states near the G-point are assigned to the combinationso fo ut-ofplane orbitals (i.e.,M o4d z 2 and S3p z )a nd have as trong interlayer coupling effect.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, because of the depletion of traditional fossil fuels and of the increasing demand for renewable energy, electrocatalytic materials that are used in electrochemical energy applications, including hydrogen production [1][2][3], supercapacitors [4], lithium-ion batteries [5][6][7], fuel cells [8], and photoelectrochemical cells [9], have received considerable attention from scientists.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, molybdenum sulfide (MoS x ; x = 2, 3) has been identified as a promising electrochemical catalyst for many electrochemical applications, including hydrogen production [1][2][3], supercapacitors [4,13], solar cells [14,15], fuel cells [8], and lithium-ion batteries [5,6]. Amorphous MoS 2 , MoS 3 , and MoS x films have been reported as heterogeneous catalysts for the hydrogen evolution reaction (HER) [1,3].…”
Section: Introductionmentioning
confidence: 99%